Drivers of the food system based on food sovereignty domains: an integrative systematic literature review - Rivera, Igor; Díaz de León, Denise; Pérez-Salazar, María del Rosario (Frontiers in Sustainable Food Systems, 2024)
Food sovereignty, as defined by the comprehensive definition offered in the 2007 Nyéléni Forum, encompasses essential action lines for transforming a food system based on food sovereignty principles. Understanding how current food system initiatives align with these principles is essential for identifying the necessary processes of change to drive this transformation. This study aimed to consolidate the contributions of advancements in food sovereignty to the existing literature. A systematic literature review was conducted to achieve this, analyzing 250 papers published between 2008 and 2023. The focus was on the research methods employed by the authors, food initiatives within the domains of food sovereignty, and the key drivers of a food system rooted in food sovereignty principles. The findings revealed that approximately 36% of the studies utilized interviews, surveys, and questionnaires for data collection, while 34% concentrated on targeted fieldwork through case studies. Around 19% of the studies involved in-depth interaction with specific groups, and just under 10% employed document analysis methods. The most extensively discussed domain was the use of agroecological management practices for food production, followed by the valuation of traditional knowledge, the promotion of social justice and equity, self-determination through the transformation of economic and political institutions, and the localization of food production and consumption. The food initiatives outlined overarching goals within each domain of food sovereignty, with three common goals identified across these domains: food security and consumption, environmental stewardship, and crisis preparedness. Furthermore, 29 drivers of a food system based on the domains of food sovereignty were identified, encompassing networks and a holistic approach present in all 5 domains. The study also highlights the implications for supporters of food sovereignty within the context of the identified goals of the food initiatives.